Morphology and molecular phylogeny of raillietina spp. (cestoda: cyclophyllidea: davaineidae) from domestic chickens in Thailand - Butboonchoo P. (2017)
© 2016, Korean Society for Parasitology and Tropical Medicine. Raillietina species are prevalent in domestic chickens (Gallus gallus domesticus) in Phayao province, northern Thailand. Their infection may cause disease and death, which affects the public health and economic situation in chicken farms. The identification of Raillietina has been based on morphology and molecular analysis. In this study, morphological observations using light (LM) and scanning electron microscopies (SEM) coupled with molecular analysis of the internal transcribed spacer 2 (ITS2) region and the nicotinamide adenine dinucleotide dehydrogenase subunit 1 (ND1) gene were employed for precise identification and phylogenetic relationship studies of Raillietina spp. Four Raillietina species, including R. echinobothrida, R. tetragona, R. cesticillus, and Raillietina sp., were recovered in domestic chickens from 4 districts in Phayao province, Thailand. LM and SEM observations revealed differences in the morphology of the scolex, position of the genital pore, number of eggs per egg capsule, and rostellar opening surface structures in all 4 species. Phylogenetic relationships were found among the phylogenetic trees obtained by the maximum likelihood and distance-based neighbor-joining methods. ITS2 and ND1 sequence data recorded from Raillietina sp. appeared to be monophyletic. The query sequences of R. echinobothrida, R. tetragona, R. cesticillus, and Raillietina sp. were separated according to the different morphological characters. This study confirmed that morphological studies combined with molecular analyses can differentiate related species within the genus Raillietina in Thailand.